Honest June - Wells, Tina, 1980-; Smith, Stephanie (Ghost writer) (Random House, 2021)
June, a girl who has always told little, she thinks harmless, lies to keep her friends and family happy, is suddenly "blessed" by her secret fairy godmother with the ability to only tell the truth. Now, with no choice but to give her honest opinion, June's stress levels skyrocket--but in time, she may learn that there is freedom when she tells the truth.